Propuesta de formalización empresarial para el taller industrial “Mi Nueva Bendición” ubicada en la ciudad de Santa Marta (2023)
From industrial engineering you can cover various areas in which the business sector occurs, one of them being the informality that often occurs in small businesses. This from various causes such as the lack of knowledge of all the benefits that carrying the requirements that the Colombian regulations ask for in companies would bring, or for the fear that they will have extra costs, thus giving these companies results of disorganization, zero protection for the employee's health and safety, more hours without any labor remuneration, among other consequences that will be mentioned in this investigation. Where, by means of an analysis, all these effects can be identified, and also an attempt will be made to structure all the formality that the business "My New Blessing" needs, which is a workshop that has the basic factors with which the company you can count. With this, a proposal will be made from the accounting to the administrative structure with which the company can enter the regulations that the country's regulations have, resulting in the necessary bases to venture and look at the benefits or advantages of giving application to it.